Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1002/alr.21802
|View full text |Cite
|
Sign up to set email alerts
|

Severity of nasal obstruction can predict the anxiety status of patients with allergic rhinitis but not patients with vasomotor rhinitis

Abstract: Nasal obstruction may play a prominent role in mediation of anxiety in patients suffering from AR, but not in patients suffering from VMR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 33 publications
0
12
1
Order By: Relevance
“…It has been verified that AR exerted significant effects on students' character, memory and sleep quality, emotion, and memory 21. Moreover, AR cases showed a greater risk of otitis media with effusion,62 Kawasaki disease,63 primary immune thrombocytopenia,64 migraine,65 attention deficit hyperactivity disorder, and oppositional defiant disorder66 in children, sleep disorder-related problems in pregnant women,67 and mental disorders in adults 68. Unfortunately, the trend of AR incidence is still on the rise and has become significant economic burden on the general public 69.…”
Section: Prospectsmentioning
confidence: 95%
“…It has been verified that AR exerted significant effects on students' character, memory and sleep quality, emotion, and memory 21. Moreover, AR cases showed a greater risk of otitis media with effusion,62 Kawasaki disease,63 primary immune thrombocytopenia,64 migraine,65 attention deficit hyperactivity disorder, and oppositional defiant disorder66 in children, sleep disorder-related problems in pregnant women,67 and mental disorders in adults 68. Unfortunately, the trend of AR incidence is still on the rise and has become significant economic burden on the general public 69.…”
Section: Prospectsmentioning
confidence: 95%
“…Nasal congestion can severely impact an individual's quality of life, particularly in subjects suffering from nasal diseases such as allergic rhinitis and chronic rhinosinusitis. Indeed, the relationship between nasal obstruction and the anxiety status of patients with allergic rhinitis has been documented recently . Since the first use of nasal airflow measurement by Kayser over 120 years ago for examination of the nasal cycle, multifarious instruments have been developed for the objective assessment of nasal airflow.…”
mentioning
confidence: 99%
“…49 Patients with AR suffer from depression, sleep problems, and anxiety status more than people without allergic disease. 6,1116 Mental disorders affect about 1 in 4 adults annually. 15 Depression is a common but serious mood disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that a relationship exists between psychological factors and atopic disorders. 6,8,1116 The goal of this study was to investigate the clinical effect of a liposomal nasal spray (LN) containing vitamins A and E on the nasal mucosa in patients suffering from AR who had refused any type of anti-allergic treatment. For this purpose, the results of nasal cytology, Visual Analog Scale (VAS), Sino-Nasal Outcome Test-22 (SNOT-22), and Hospital Anxiety and Depression Scale (HADS) test were analyzed.…”
Section: Introductionmentioning
confidence: 99%